The dynamics of the condition of athletes depending on organization of training activities high-speed power orientation - Yuantsyuan, P.; Kozhedub M. S.; Vrublevskiy E. P. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to discern objective trends that reveal the correlation between the performance of female sprinters and the extensive training regimen they undergo in speed and strength training during the initial phases of the annual cycle.